The effect of project based learning approach on undergraduate students' environmental problem solving skills [Proje tabanlı öǧrenme yaklaşımının lisans öǧrencilerinin çevreye yönelik problem çözme becerilerine etkisi] - (:unkn) unknown (Ankara University, 2013)
Environmental problem solving skills cover identifying environmental problems, being aware of these problems, research of the reasons and identifying alternative ways to solve problems with solutions in different areas integrating ability to use interdisciplinary method. The purpose of this study was to investigate whether there is an effect of project-based learning approach on the development of undergraduate students' environmental problem-solving skills. Pretest and posttest control group design model is applied. The data was obtained by questioning student before and after the environmental education courses, prepared according to the project-based learning approach. As a result of assessment there was found a positive impact of project-based learning approach on the development of problem-solving skills of students.
Keywords: Environmental problem solving skills; Project based learning; Science education